Effects of a five-year citywide intervention program to control Aedes aegypti and prevent dengue outbreaks in northern Argentina. - Ricardo E Gürtler (Public Library of Science (PLoS), 2009)
Background Dengue has propagated widely through the Americas. Most countries have not been able to maintain permanent larval mosquito control programs, and the long-term effects of control actions have rarely been documented. Methodology The study design was based on a before-and-after citywide assessment of Aedes aegypti larval indices and the reported incidence of dengue in Clorinda, northeastern Argentina, over 2003-2007. Interventions were mainly based on focal treatment with larvicides of every mosquito developmental site every four months (14 cycles), combined with limited source reduction efforts and ultra-low-volume insecticide spraying during emergency operations. The program conducted 120,000 house searches for mosquito developmental sites and 37,000 larvicide applications. Principal findings Random-effects regression models showed that Breteau indices declined significantly in nearly all focal cycles compared to pre-intervention indices clustered by neighborhood, after allowing for lagged effects of temperature and rainfall, baseline Breteau index, and surveillance coverage. Significant heterogeneity between neighborhoods was revealed. Larval indices seldom fell to 0 shortly after interventions at the same blocks. Large water-storage containers were the most abundant and likely to be infested. The reported incidence of dengue cases declined from 10.4 per 10,000 in 2000 (by DEN-1) to 0 from 2001 to 2006, and then rose to 4.5 cases per 10,000 in 2007 (by DEN-3). In neighboring Paraguay, the reported incidence of dengue in 2007 was 30.6 times higher than that in Clorinda. Conclusions Control interventions exerted significant impacts on larval indices but failed to keep them below target levels during every summer, achieved sustained community acceptance, most likely prevented new dengue outbreaks over 2003-2006, and limited to a large degree the 2007 outbreak. For further improvement, a shift is needed towards a multifaceted program with intensified coverage and source reduction efforts, lids or insecticide-treated covers to water-storage containers, and a broad social participation aiming at long-term sustainability.